Evaluation of Xpert Carba-R for detecting carbapenemase-producing organisms in South Africa - Sanelisiwe T. Duze; Teena Thomas; Tshegofatso Pelego; Sabelle Jallow; Olga Perovic; Adriano Duse (AOSIS, 2023)
This study evaluated the performance of the Xpert Carba-R assay for detecting the five common carbapenemases in carbapenemase-producing organisms in Johannesburg, South Africa between April 2021 and September 2021. The assay demonstrated 98% sensitivity and 97% specificity. It was also able to detect all the carbapenemases in double carbapenemase producers, as well as carbapenemases in non-fermenter organisms. The Xpert Carba-R assay, therefore, allows the rapid ( 1 h) and accurate identification of the common carbapenemases in pure bacterial cultures and rectal swabs. This assay can aid in the timeous institution of appropriate treatment and infection prevention and control measures.